Global University Rankings and the Politics of Knowledge - Stack, Michelle, 1967- (Book collections on Project MUSE., 2021)
"For many institutions, to ignore your university's ranking is to become invisible, a risky proposition in a competitive search for funding and talent. But rankings tell us little if anything about the education, scholarship or engagement with communities offered by a university. Drawing on a range of research and inquiry-based methods, Global University Rankings and the Politics of Knowledge this book exposes how universities became servants to the education industry and its impact. Conceptually unique in its scope, Global University Rankings and the Politics of Knowledge addresses the lack of empirical research behind university and journal ranking products systems. Chapters from internationally recognized scholars in decolonial studies provide readers with robust frameworks to understand the intersections of coloniality and Indigeneity and how they play out in higher education. Including contributions from diverse geographical and disciplinary contexts, this book explores the political economy of rankings within the contexts of the Global North and South, as well as examines alternatives to media-driven rankings. This book allows readers to consider the intersections of power and knowledge within the wider contexts of politics, culture, and the economy, to explore how assumptions about different factors such as gender, social class, sexuality, and race, underpin the meanings attached to rankings, and to imagine a future that confronts and challenges cognitive, environmental, and social injustice."--